12.4k views
0 votes
Solve the equation g^2-12g=-36​

User Dayanara
by
4.7k points

2 Answers

1 vote

Let us begin by writing the given equation:

g² - 12g = - 36

Bringing all the terms to LHS for getting a quadratic equation,

g² - 12g + 36 = 0

Splitting the middle term,

g² - 6g - 6g + 36 = 0

Taking out common factors,

g ( g - 6 ) - 6 ( g - 6 ) = 0

Taking out common factors,

( g - 6 ) ( g - 6 ) = 0

( g - 6 )² = 0

( g - 6 ) = √0

g - 6 = 0

g = 6

Hence, after solving we get, g = 6

User Myrna
by
4.9k points
2 votes


\bold{Answer}


\boxed{\bold{G \ = \ 6}}


\bold{Explanation}


  • \bold{Solve: \ g^2-12g=-36}


\bold{---------------------}


  • \bold{Add \ 36 \ To \ Both \ Sides}


\bold{g^2-12g+36=-36+36}


  • \bold{Simplify}


\bold{g^2-12g+36=0}


  • \bold{Solve \ With \ Quadratic \ Formula}

  • \bold{a=1,\:b=-12,\:c=36:\quad g_(1,\:2)=(-\left(-12\right)\pm √(\left(-12\right)^2-4\cdot \:1\cdot \:36))/(2\cdot \:1)}


\bold{\left(-12\right)^2-4\cdot \:1\cdot \:36 \ = \ 0}


\bold{g_(1,\:2)=(-\left(-12\right)\pm √(0))/(2\cdot \:1)}


\bold{g=(-\left(-12\right))/(2\cdot \:1)}


  • \bold{Simplify \ (-\left(-12\right))/(2\cdot \:1) \ = \ 6}


\bold{g=6}


\boxed{\bold{Eclipsed}}

User Tanoro
by
6.0k points